Slavery, the Hebrew Bible and the Development of Racial Theories in the Nineteenth Century - Burrell, Kevin (Religions, 2021)
Racial ideas which developed in the modern west were forged with reference to a Christian worldview and informed by the Bible, particularly the Old Testament. Up until Darwin’s scientific reframing of the origins debate, European and American race scientists were fundamentally Christian in their orientation. This paper outlines how interpretations of the Hebrew Bible within this Christian Weltanschauung facilitated the development and articulation of racial theories which burgeoned in western intellectual discourse up to and during the 19th century. The book of Genesis was a particular seedbed for identity politics as the origin stories of the Hebrew Bible were plundered in service of articulating a racial hierarchy which justified both the place of Europeans at the pinnacle of divine creation and the denigration, bestialization, and enslavement of Africans as the worst of human filiation. That the racial ethos of the period dictated both the questions exegetes posed and the conclusions they derived from the text demonstrates that biblical interpretation within this climate was never an innocuous pursuit, but rather reflected the values and beliefs current in the social context of the exegete.